2016
DOI: 10.1159/000448295
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Folate Supplementation on Carotid Intima-Media Thickness and Metabolic Status in Patients with Metabolic Syndrome

Abstract: Background: This study was carried out to evaluate the effects of folate supplementation on carotid intima-media thickness (CIMT) and metabolic status among patients with metabolic syndrome (MetS). Methods: This randomized, double-blind, placebo-controlled trial was conducted among 60 patients with type 2 diabetes mellitus and coronary heart disease. They were all overweight in the age range 40-85 years. Participants were randomly divided into 2 groups: group A (n = 30) received 5 mg folate supplements and gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…In addition, lower folate concentrations, but not restricted to folate deficiency, are associated with higher rates of all-cause, CVD, and cancer mortality [13]. Few studies have evaluated the effects of folate on markers of insulin metabolism among patients with MetS [14], women with PCOS [15], and subjects with T2DM [16]; however, findings were controversial. Such inconsistent findings complicate approaches to prescribe folate for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, lower folate concentrations, but not restricted to folate deficiency, are associated with higher rates of all-cause, CVD, and cancer mortality [13]. Few studies have evaluated the effects of folate on markers of insulin metabolism among patients with MetS [14], women with PCOS [15], and subjects with T2DM [16]; however, findings were controversial. Such inconsistent findings complicate approaches to prescribe folate for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, PICRUSt analysis showed that 3DG caused the downregulation of carbohydrate metabolism and amino acid metabolism, suggesting that metabolic function is inhibited in 3DG-induced prediabetic rats. Metabolism of cofactors and vitamin disorders such as the downregulation of folate metabolism (a kind of diabetes biomarker) increased the risk of metabolic diseases [ 35 ]. Previous research found a decrease in functions involving cofactor and vitamin metabolism and amino acid metabolism in metabolic diseases such as T2D and obesity [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…CIMT measurement obtained in both the left and right carotid artery and mean CIMT was calculated as the mean of the left and the right measurements [36]. There are different tools for measurement of CIMT including the B-mode ultrasonography (Accuvix V10, Medison) for a specialist radiologist [37], and a high-resolution ultrasonographic scanner (Vivid S6; GE Healthcare, Horton, Norway) equipped with a 10-MHz linear-array transducer [1] and a Doppler ultrasonography device (Samsung Medison V20) with linear multi frequencies of 7.5-10 MHz probe [38].…”
Section: Measurement Of Carotid Intima-media Thicknessmentioning
confidence: 99%